If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2m + -12) + -1(-9m + -7) = 0 Reorder the terms: (-12 + 2m) + -1(-9m + -7) = 0 Remove parenthesis around (-12 + 2m) -12 + 2m + -1(-9m + -7) = 0 Reorder the terms: -12 + 2m + -1(-7 + -9m) = 0 -12 + 2m + (-7 * -1 + -9m * -1) = 0 -12 + 2m + (7 + 9m) = 0 Reorder the terms: -12 + 7 + 2m + 9m = 0 Combine like terms: -12 + 7 = -5 -5 + 2m + 9m = 0 Combine like terms: 2m + 9m = 11m -5 + 11m = 0 Solving -5 + 11m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 11m = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 11m = 0 + 5 11m = 0 + 5 Combine like terms: 0 + 5 = 5 11m = 5 Divide each side by '11'. m = 0.4545454545 Simplifying m = 0.4545454545
| (x+(3+5i))(x+(3-5i))=0 | | (x+(3+5i))(x-(3-5i))=0 | | 5(7-w)+5w=36 | | 3(6u+8)=16u+20 | | 3x-12=8+3x | | √(12y)1/2 | | (x+5)+x=90 | | 15*3.1415926535897932384626433832795= | | 2z(2z+1)(5z-4)= | | 6/7/42/5 | | -3(w+6)+30=3(4-w) | | 3(7-y)+2y=13 | | 32=10logx | | a-20=b | | 2y+6=-10y+30 | | 5(3v+4)=13v+32 | | 1+3(d+2)=d+2(d-4) | | x/36=12/72 | | -4(w+3)+33=4(6-w) | | 2(x-2)=-11 | | 42-6x=0 | | -294=7(6-6a) | | 6-5lnx=5 | | 2lnx=ln(3x+10) | | 4(8k-5)=-180 | | 0=-43c | | 2x+x-4=30 | | Y=-x^2-3x+18 | | log(x/0.15)=5 | | x^2+1.4x-13.95=0 | | v=4/3×3.14r^3 | | 5(6-y)+7y=16 |